ACADEMIC PROCRASTINATION REVIEWED FROM SEX DISTINCTION ON KEMENKES POLYTECHNIC STUDENT SEMARANG - Kristiandani, Roy Hendra; Dewi, Endah Kumala (Empati, 2013)
Academic procrastination is delay which performed on the formal tasks related to academic assignments or academic performance. Procrastination which is done by the students is influenced by two factors, namely internal and external factors. Academic procrastination from the standpoint of gender isn’t escape from the factors that influence subjectdevelopment, i.e. student developments, covering the physical, psychological, social roles, gender roles, and religious developments.This research aimed to determine differences in the level of academic procrastination based on gender male and female in the Kemenkes Health Polytechnic Semarang students. Subjects in this research amounted 60 male and 60 female students.Sampling was done using proportional random sampling method. Data in this research were collected using psychological scales, i.e. scale of academic procrastination. Hypothesis test used T - test analysismethod.Based on the analysis of data obtained from t – test, result of t value = -3.718 at a significance level of 0.00 (p < 0.05). Based on the meanof difference level of academic procrastinationshowed the mean value of female students was 53.38 and male was 58.98 that is in the range of 47.25 to 67.5. This indicated that the hypothesis can be accepted, namely that male students have higher level of academic procrastination compared with female students.